DETERMINANTS OF FINANCIAL SUSTAINABILITY FOR MICRO, SMALL, AND MEDIUM ENTERPRISES IN THE CITY OF CIMAHI - Siti Kustinah, Siti Kustinah; Winarso, Eddy (Jurnal Riset Bisnis dan Manajemen, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a role in economic development and human resources competencies, revenue diversification strategies, cost management practices, and employment absorption, 2022 more than 65 million and contributing to Gross Domestic Product (GDP) by 61% equivalent to IDR 9,580 trillion and absorbing almost 97% of the workforce equivalent to 117 million workers. Associated with the Sustainable Development Goals (SDG), this study includes: SDG 1 ending poverty, SDG 2 ending hunger, SDG 3 good health and well-being, SDG 5 gender equality, SDG 8 inclusive and sustainable economic growth, and SDG 9 increasing sustainable industrialization and encouraging innovation. The study analyzed the factors that influence financial sustainability in MSMEs in Cimahi City, including financial sustainability. The results of the study: human resources competencies, revenue diversification strategies, and cost management practices partially and simultaneously have a positive and significant effect on the financial sustainability of MSMEs in Cimahi City.